Social identity and psychosis: Explaining elevated rates of psychosis in migrant populations. Issue 11 (November 2016) - McIntyre, Jason C.; Elahi, Anam; Bentall, Richard P.
Abstract: A substantial body of literature suggests that migrants are at greater risk of developing psychotic symptoms, such as paranoia, compared to non‐migrants. To date, researchers have been unable to identify the primary cause of this effect, finding scarce support for biological, diagnostic, and economic explanations. Social determinants have received little empirical attention in this domain, which we assert is a critical gap in the literature. Here, we propose that the social identity approach offers a framework to help explain the elevated rates of psychosis among migrants, and in turn inform policies and interventions to address this important mental health issue. We propose that cultural identities play a central role in mitigating the psychological precursors of psychosis and that disidentification and social disconnection subsequent to migration could initiate or exacerbate psychosis for multiple generations. We draw together research from social and clinical psychology to detail a social identity approach to psychosis in migrant populations, and make recommendations for future research.